n-3 PUFA ameliorate functional outcomes following repetitive mTBI in the fat-1 mouse model - Lau, Jessi S.; Lust, Cody A. C.; Lecques, Jessica-Dominique; Hillyer, Lyn M.; Mountjoy, Margo; Kang, Jing X.; Robinson, Lindsay E.; Ma, David W. L. (Frontiers in Nutrition, 2024)
Purpose Repeated mild traumatic brain injuries (mTBI) are a continuing healthcare concern worldwide, given its potential for enduring adverse neurodegenerative conditions. Past research suggests a potential protective effect of n-3 polyunsaturated fatty acids (PUFA) in experimental models of mTBI. The aim of this study was to investigate whether the neuroprotective benefits of n-3 PUFA persist following repetitive weight drop injury (WDI). Methods Male fat-1 mice (n = 12), able to endogenously convert n-6 PUFA to n-3 PUFA, and their wild type (WT) counterparts (n = 12) were maintained on a 10% w/w safflower diet. At 9–10 weeks of age, both groups received one mild low-impact WDI on the closed cranium daily, for three consecutive days. Following each WDI, time to righting reflex and seeking behaviour were measured. Neurological recovery, cognitive, motor, and neurobehavioural outcomes were assessed using the Neurological Severity Score (NSS) over 7 days (168 h) post-last WDI. Brains were assessed for cerebral microhemorrhages by Prussian blue and cellular damage by glial fibrillary acidic protein (GFAP) staining. Results Fat-1 mice exhibited significantly faster righting reflex and seeking behaviour time, and lower mean NSS scores and at all post-WDI time points (p ≤ 0.05) compared to WT mice. Immunohistochemistry showed no significant difference in presence of cerebral microhemorrhage however, fat-1 mice had significantly lower GFAP staining in comparison to WT mice (p ≤ 0.05). Conclusion n-3 PUFA is effective in restoring cognitive, motor, and behavioural function after repetitive WDI, which may be mediated through reduced cellular damage of the brain.